Brain responses to chronic social defeat stress: effects on regional oxidative metabolism as a function of a hedonic trait, and gene expression in susceptible and resilient rats. - Kanarik, M; Alttoa, A; Matrov, D; Kõiv, K; Sharp, T; Panksepp, J; Harro, J (2011)
Chronic social defeat stress, a depression model in rats, reduced struggling in the forced swimming test dependent on a hedonic trait-stressed rats with high sucrose intake struggled less. Social defeat reduced brain regional energy metabolism, and this effect was also more pronounced in rats with high sucrose intake. A number of changes in gene expression were identified after social defeat stress, most notably the down-regulation of Gsk3b and Map1b. The majority of differences were between stress-susceptible and resilient rats. Conclusively, correlates of inter-individual differences in stress resilience can be identified both at gene expression and oxidative metabolism levels.